EKSKLUSIVISME BAHAUDDIN NURSALIM: Radikalisasi dan Ideologisasi Ayat Interagama di Youtube - Fikri Fanani; Agus Harianto (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2022)
The development of da'wah in modern times is different from ancient times. At this time the media of da'wah has shifted to the virtual world, an electronic world in computer networks that are widely used as online communication. Youtube is a video sharing website created by 3 former PayPal employees in 2005. The site provides facilities for the public to upload, watch and share videos. Besides being used as a money maker, Youtube is currently also used as a tool to spread religious ideology. One of the cleric figures that has gone viral on the Youtube site is Bahauddin Nursalim, who is more familiarly called Gus Baha. In the last two years, his name has drastically popped into the arena of religious scholarly discourse. His deep knowledge and captivating rhetoric make it easy for him to fill the hearts of the audience. This paper wants to identify the reasoning side of Bahauddin Nursalim's thinking and ideology. Even though he doesn't have a personal channel, the recitation videos he fills in as well as public lectures have been widely spread on the channels of his congregation. Therefore, the primary sources of this mini-research are 5 video lectures of Bahauddin Nursalim. As for theoretically, the author uses the theory of language criticism popularized by Roger Flower and his friends.